2020
DOI: 10.1186/s40594-020-00211-w
|View full text |Cite
|
Sign up to set email alerts
|

Increasing high school teachers self-efficacy for integrated STEM instruction through a collaborative community of practice

Abstract: Background: Teachers can have a significant impact on student interest and learning in science, technology, engineering, and math (STEM) subjects and careers. Teacher self-efficacy can also significantly affect student learning. Researchers investigated the effects of teacher professional development and integrated STEM curriculum development on teacher self-efficacy. Participants in the study included high school science and engineering technology teachers enrolled in a National Science Foundation-ITEST proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 27 publications
5
95
0
3
Order By: Relevance
“…One of the main goals of the workshop series was to increase teachers' motivation for and confidence in engineering instruction. As earlier research has shown, increased self-efficacy often leads to successful STEM integration in the classroom (Kelley et al 2020). Principally based on the situative perspective of learning (Putnam and Borko 2000), the workshops allowed teachers to participate in the same modeled engineering tasks intended for their students.…”
Section: Motivation and Confidence To Integrate Engineering Instructionmentioning
confidence: 99%
“…One of the main goals of the workshop series was to increase teachers' motivation for and confidence in engineering instruction. As earlier research has shown, increased self-efficacy often leads to successful STEM integration in the classroom (Kelley et al 2020). Principally based on the situative perspective of learning (Putnam and Borko 2000), the workshops allowed teachers to participate in the same modeled engineering tasks intended for their students.…”
Section: Motivation and Confidence To Integrate Engineering Instructionmentioning
confidence: 99%
“…Efficacy for designing STEM e-learning refers to the belief of a person about his/her ability to work effectively through specific instructional design processes (Collier, 2002 ; Thibaut et al, 2018 ). Efficacy of teachers extends beyond their perceived personal capabilities to a more general view of their preparedness for teaching and affecting the desired student learning (Ross and Bruce, 2007 ; Settlage et al, 2009 ; Kelley et al, 2020 ). Efficacy of teachers for designing STEM learning can thus be considered as their self-expectations that they will be able to design tasks that require students to use STEM knowledge and skills in the context of complex situations or problem-solving processes (Honey et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research provides some evidence that teacher CoP can foster social spaces for identity development, self-efficacy growth, and therefore, retention in the profession (Goos & Bennison, 2008;Kelley, Knowles, Holland, & Han, 2020;Simpson & Bouhafa, 2020). For instance, research suggests that a supportive, collaborative work environment with cohesion among education stakeholders lowers the likelihood of teacher attrition (Billingsley, 2004;Buchanan, 2012;Hausman & Goldring, 2001;Mack, Johnson, Jones-Rincon, Tsatenawa, & Howard, 2019).…”
Section: A Community Of Practice Is a Specific Type Of Social Networkmentioning
confidence: 99%
“…For instance, research suggests that a supportive, collaborative work environment with cohesion among education stakeholders lowers the likelihood of teacher attrition (Billingsley, 2004;Buchanan, 2012;Hausman & Goldring, 2001;Mack, Johnson, Jones-Rincon, Tsatenawa, & Howard, 2019). In a recent study, Kelley et al (2020) found that teachers who participated in a STEM community of practice increased their selfefficacy related to teaching. Regarding identity, Luehmann (2007) discussed CoP as a "safe space" (p. 828) where teachers discover, construct, and try new identities.…”
Section: A Community Of Practice Is a Specific Type Of Social Networkmentioning
confidence: 99%